A brain signature for acute pain - Apkarian, A. Vania (2013)
Wager and colleagues developed an fMRI-based spatial and magnitude pattern for perception of acute pain, which seems to generalize across many task conditions and subjects. This is a strong demonstration of the existence of a pain signature and raises important questions regarding what pain and perception are.